Assessment of the agronomic performance of twenty-two (22) peanut (Arachis hypogaea L.) accessions against late leaf spot and groundnut rosette diseases in central Côte d'Ivoire - N'Gbesso, Mako François De Paul; Gadji, Alahou André Gabaze; Coulibaly, Noupé Diakaria; Kogloin, Boua Urbain; Fondio, Lassina; Ossey, Christian-Landry; N'Gaza, Aya Félicité; Tienebo, Eric-Olivier; Abo, Kouabenan (Cogent food & agriculture, 2024)
Late leaf spot and groundnut rosette are major constraints to groundnut cultivation, especially in the second crop cycle in central Côte d'Ivoire. This study was initiated to improve peanut production. It was conducted on 22 peanut accessions using a randomized complete block design with three (03) replications. In each elementary plot, agromorphological, and health parameters were assessed on ten plants per accession. A symptom rating scale was used to assess disease severity. The results showed that the agromorphological parameters were higher in the first cycle than in the second. Accessions ARA42, ARA60, ARA56, and ARA51, moderately resistant or tolerant to groundnut rosette and susceptible to late leaf spot, gave the best seed yields in the second cycle, which varied between 1.42 and 1.59 tons per hectare (t/ha). Those highly susceptible to these parasitic diseases (ARA55, ARA40, ARA39, ARA54, ARA57, and ARA53) gave the lowest yields ranging from 0.131 to 0.996 t/ha over the same period. Groundnut rosette and late leaf spot attacks were less severe in the first crop cycle than in the second, with mean severity ranging from 36.5 to 51.5% and 24.9 to 55.5%, respectively. Accessions ARA42, ARA60, ARA56, and ARA51 should be the subject of a rigorous selection program and made available to growers. As a result, yield losses during the second crop cycle, from July to October, will be reduced, and the use of synthetic chemical pesticides in peanut cultivation will be limited. The manuscript reveals the biotic constraints linked to groundnut production in the second crop cycle between July and October. This document is important for public authorities, development and groundnut sector stakeholders and small-scale producers who make a living from this activity. The article shows that production losses in the second crop cycle are more than 60%. But these losses can be reduced or mitigated by using resistant or tolerant genotypes. To this end, this paper presents resistant or tolerant groundnut varieties that can be used in the second crop cycle to limit production losses. Given the importance of groundnuts in cropping systems, in the agri-food industry, for human and animal consumption, for medicinal purposes and as a source of income for small-scale producers, this article provides an opportunity to produce groundnuts over both cropping cycles (March to June and July to October).